2016
DOI: 10.1186/s12934-016-0544-1
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of the fungal d-galacturonate pathway enables the consumption of d-galacturonic acid by Saccharomyces cerevisiae

Abstract: BackgroundPectin-rich wastes, such as citrus pulp and sugar beet pulp, are produced in considerable amounts by the juice and sugar industry and could be used as raw materials for biorefineries. One possible process in such biorefineries is the hydrolysis of these wastes and the subsequent production of ethanol. However, the ethanol-producing organism of choice, Saccharomyces cerevisiae, is not able to catabolize d-galacturonic acid, which represents a considerable amount of the sugars in the hydrolysate, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…We found that d -galacturonate reductase from Trichoderma reesei (GAR1) and 2-keto-3-deoxy-L-galactonate aldolase from Aspergillus niger (GAAC) have activities near the rate-limiting specific activity of glycolysis: 0.1 µmol min −1 mg −1 protein (Supplementary Table 2 ) 32 . However, consistent with previous reports 26 , 28 , we observed very low activity for the three L-galactonate dehydratase (LGD1) enzymes tested. To allow for facile detection of dehydratase expression, we N-terminally tagged the T. reesei LGD1 with a yellow fluorescent protein (Venus).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We found that d -galacturonate reductase from Trichoderma reesei (GAR1) and 2-keto-3-deoxy-L-galactonate aldolase from Aspergillus niger (GAAC) have activities near the rate-limiting specific activity of glycolysis: 0.1 µmol min −1 mg −1 protein (Supplementary Table 2 ) 32 . However, consistent with previous reports 26 , 28 , we observed very low activity for the three L-galactonate dehydratase (LGD1) enzymes tested. To allow for facile detection of dehydratase expression, we N-terminally tagged the T. reesei LGD1 with a yellow fluorescent protein (Venus).…”
Section: Resultssupporting
confidence: 93%
“…Several attempts at engineering S. cerevisiae as a host for d -galUA fermentations have been published, yet a strain capable of growing on this sugar as the primary carbon source or co-consuming d -galUA with d -glucose have not yet been reported 24 – 27 . Efforts to enable growth on d -galUA using a fungal catabolic pathway have been impaired by low specific activity of enzymes within the pathway, particularly the l -galactonate dehydratase step 26 , 28 . Additionally, S. cerevisiae lacks a dedicated transport system for d -galUA and import inhibition of d -galUA by d -glucose has not been described prior to this report.…”
Section: Introductionmentioning
confidence: 99%
“…b Engineered S. cerevisiae strains expressing D-GalA membrane transporter Gat1 from Neurospora crassa and the uronate dehydrogenase (UDH) from Agrobacterium tumefaciens and D-galacturonic acid reductase (GAAA) from Aspergillus niger to convert D-GalA into the metabolites meso-galactaric acid and L-galactonate, (Benz et al 2014). c Engineered S. cerevisiae strain with Dgalacturonic acid plasma membrane transporters from N. crassa (GAT1) and enzymes of the D-GalA catabolic pathway GaaA, GaaB, GaaC and GaaD from A. niger (in green) and LGD1 from Trichoderma reesei (in purple); D-Fructose was used as co-substrate (Biz et al 2016). d Engineered S. cerevisiae strains with the non-glucose repressible plasma membrane D-galacturonic acid transporter GatA from A. niger (GATA) and D-GalA catabolic pathway as in c); D-glucose was used as co-substrate (Protzko et al 2018) dependent enzymes: the D-galacturonate reductase and the Lglyceraldehyde reductase, for the catabolisation of Dgalacturonic acid into glycerol (Biz et al 2016) (Fig.…”
Section: The Challengesmentioning
confidence: 99%
“…c Engineered S. cerevisiae strain with Dgalacturonic acid plasma membrane transporters from N. crassa (GAT1) and enzymes of the D-GalA catabolic pathway GaaA, GaaB, GaaC and GaaD from A. niger (in green) and LGD1 from Trichoderma reesei (in purple); D-Fructose was used as co-substrate (Biz et al 2016). d Engineered S. cerevisiae strains with the non-glucose repressible plasma membrane D-galacturonic acid transporter GatA from A. niger (GATA) and D-GalA catabolic pathway as in c); D-glucose was used as co-substrate (Protzko et al 2018) dependent enzymes: the D-galacturonate reductase and the Lglyceraldehyde reductase, for the catabolisation of Dgalacturonic acid into glycerol (Biz et al 2016) (Fig. 3c) leading to intracellular cofactor imbalance.…”
Section: The Challengesmentioning
confidence: 99%
See 1 more Smart Citation